Analysing participants' performance in idea generation meeting considering emotional context-aware - Carneiro, João (2012)
In an idea generation meeting the emotional context-aware is correlated the with participants’ performance. To achieve good results in idea generation sessions it is important that participants maintain a positive emotional state. In this paper we will present an agent-based idea generation meeting using an emotional context-aware model that includes several mechanisms, namely: the analysis and evaluation of events, emotion-based process and recommendation selection. In order to analyse and test the benefits of these mechanisms, we also created a simulated scenario where agents generate ideas and are affected by context-aware situations. The simulation reveals that these mechanisms can increase the participants’ performance using some techniques. This study shows how the use of recommendation mechanisms can maximize meeting results in some situations.